2022
DOI: 10.1038/s41420-022-00816-w
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidin hCAP18/LL-37 promotes cell proliferation and suppresses antitumor activity of 1,25(OH)2D3 in hepatocellular carcinoma

Abstract: Cathelicidin hCAP18/LL-37 can resist infection from various pathogens and is an essential component of the human immune system. Accumulating evidence has indicated that hCAP18/LL-37 plays a tissue-specific role in human cancer. However, its function in hepatocellular carcinoma (HCC) is poorly understood. The present study investigated the effects of hCAP18/LL-37 on HCC in vitro and in vivo. Results showed that hCAP18/LL-37 overexpression significantly promoted the proliferation of cultured HCC cells and the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…However, contradictory results have been shown for LL-37 linked to cancers in different models. The existing data indicate that LL-37 can exert a tumorigenic effect in some cancers, including lung cancer, breast cancer, ovarian cancer, melanoma, prostate cancer, liver cancer, and skin squamous cell carcinoma ( Coffelt et al, 2009 ; Cha et al, 2016 ; Muñoz et al, 2016 ; Wang et al, 2017 ; Habes et al, 2019 ; Jiang et al, 2020 ; Ding et al, 2021 ; Zhang et al, 2022 ). Mechanistically, LL-37 activated Wnt/β-catenin signaling by inducing the phosphorylation of protein kinase B and subsequent phosphorylation of glycogen synthase kinase 3β mediated by the toll-like receptor-4 expressed in lung tumor cells ( Ji et al, 2019 ).…”
Section: How Ll-37 Can Eradicate/affect Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…However, contradictory results have been shown for LL-37 linked to cancers in different models. The existing data indicate that LL-37 can exert a tumorigenic effect in some cancers, including lung cancer, breast cancer, ovarian cancer, melanoma, prostate cancer, liver cancer, and skin squamous cell carcinoma ( Coffelt et al, 2009 ; Cha et al, 2016 ; Muñoz et al, 2016 ; Wang et al, 2017 ; Habes et al, 2019 ; Jiang et al, 2020 ; Ding et al, 2021 ; Zhang et al, 2022 ). Mechanistically, LL-37 activated Wnt/β-catenin signaling by inducing the phosphorylation of protein kinase B and subsequent phosphorylation of glycogen synthase kinase 3β mediated by the toll-like receptor-4 expressed in lung tumor cells ( Ji et al, 2019 ).…”
Section: How Ll-37 Can Eradicate/affect Cancer?mentioning
confidence: 99%
“…A number of studies have reported that LL-37 exerts a diverse range of pleiotropic attributes including antimicrobial activities, immunity, angiogenesis, wound repair, and bone tissue engineering ( Tjabringa et al, 2003 ; Elssner et al, 2004 ; Bucki et al, 2010 ; Pfosser et al, 2010 ; Ramos et al, 2011 ; Liu et al, 2018 ; Mitchell et al, 2022 ). However, different from its traditional roles, emerging evidence from cancer biology studies suggests that LL-37 might promote or inhibit tumor progression ( Ren et al, 2012 ; Piktel et al, 2016 ; Chen et al, 2018 ; Jiang et al, 2020 ; Chen et al, 2021 ; Vitale et al, 2021 ; Kiatsurayanon et al, 2022 ; Zhang et al, 2022 ). LL-37 plays an important and complex role in the regulation of different human cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research demonstrated that hCAP18/LL-37 has a promotional effect on HCC cell proliferation and tumor growth both in vitro and in vivo [ 19 ]. Furthermore, hCAP18/LL-37 expression can be significantly induced by 1,25(OH) 2 D 3 in HCC cells and in xenograft tumor tissue, which in turn suppresses the antitumor growth activity of 1,25(OH) 2 D 3 in HCC xenograft tumors.…”
Section: Introductionmentioning
confidence: 99%
“…25(OH)D produces antimicrobial peptides, including human antimicrobial peptide LL-37 and human β-defensin-2, by activating vitamin D receptors and binding to vitamin D effector element target genes during pathogen infection (4). LL-37 is the only human endogenous antimicrobial peptide in the cathelicidin family that has been discovered so far (5), and it shows a wide range of antibacterial activity against bacteria, viruses, and fungi (6) along with immunomodulatory and chemotactic effects (7,8), it is named LL -37 because it contains two lysine residues (L) before the N-terminus, and consists of 37 amino acids (9). The promoter region of LL -37 gene contains a TAAA sequence, an interleukin 6 nuclear factor -6 (NF -IL -6) binding site, and three acute phase response factors (APRF), which can bind to inflammatory factors, thereby increasing LL -37 gene expression levels (10).…”
Section: Introductionmentioning
confidence: 99%